Development of Islamic Education ‎Management Based on Cyber Pedagogy: Case ‎Study in Vocational High School - Nur Cholid; Linda Indiyarti Putri; Mirza Mahbub Wijaya; Mohd. Tahseen Zaman (TADRIS: Jurnal Pendidikan Islam, 2023)
This study explores cyber pedagogy potential under Islamic education management in vocational school. This study intends to investigate how to support teachers' professional development and mindset enhancement; the implemention; and the way in overcoming obstacles of cyber pedagogy. This research adopts a qualitative field research design with a phenomenological approach. Meanwhile, this study was conducted at Muhammadiyah Kajen Vocational School. This research’s primary data collection methods were observation, documentation, and in-depth interviews, involving six key informants, including stakeholders and teaching staff. The findings reveal that All aspects of educational systems, such as technology proficiency, mindset, and learning design, should be supported by this curriculum. Meanwhile, four steps can be taken to implement cyber-based leaning. The first strategy involves mapping knowledge and skills to needs. Second, the school needs to evaluate students and keep an eye on their performance. Third on the list is developing training based on needs analysis, which is followed by continuous programme assessment and monitoring. In the meantime, this programme adds to certain issues. SMK Muhammadiyah Kajen is noteworthy for its ability to cultivate a digital mindset through the integration of human resources into a digital setting, resulting in a cutting edge, inventive, and contemporary learning environment.